Urinary chemokine C-X-C motif ligand 16 and endostatin as predictors of tubulointerstitial fibrosis in patients with advanced diabetic kidney disease. Issue 2 (10th October 2019) - Lee, Yu Ho; Kim, Ki Pyo; Park, Sun-Hwa; Kim, Dong-Jin; Kim, Yang-Gyun; Moon, Ju-Young; Jung, Su-Woong; Kim, Jin Sug; Jeong, Kyung-Hwan; Lee, So-Young; Yang, Dong-Ho; Lim, Sung-Jig; et al.
Abstract: Background: Interstitial fibrosis and tubular atrophy (IFTA) is a well-recognized risk factor for poor renal outcome in patients with diabetic kidney disease (DKD). However, a noninvasive biomarker for IFTA is currently lacking. The purpose of this study was to identify urinary markers of IFTA and to determine their clinical relevance as predictors of renal prognosis. Methods: Seventy patients with biopsy-proven isolated DKD were enrolled in this study. We measured multiple urinary inflammatory cytokines and chemokines by multiplex enzyme-linked immunosorbent assay in these patients and evaluated their association with various pathologic features and renal outcomes. Results: Patients enrolled in this study exhibited advanced DKD at the time of renal biopsy, characterized by moderate to severe renal dysfunction [mean estimated glomerular filtration rate (eGFR) 36.1 mL/min/1.73 m 2 ] and heavy proteinuria (mean urinary protein:creatinine ratio 7.8 g/g creatinine). Clinicopathologic analysis revealed that higher IFTA scores were associated with worse baseline eGFR (P < 0.001) and poor renal outcome (P = 0.002), whereas glomerular injury scores were not. Among measured urinary inflammatory markers, C-X-C motif ligand 16 (CXCL16) and endostatin showed strong correlations with IFTA scores (P = 0.001 and P < 0.001, respectively), and patients with higher levels of urinary CXCL16 and/or endostatin experienced significantly rapid renal progression compared with other patients (P < 0.001). Finally, increased urinary CXCL16 and endostatin were independent risk factors for poor renal outcome after multivariate adjustments (95% confidence interval 1.070–3.455, P = 0.029). Conclusions: Urinary CXCL16 and endostatin could reflect the degree of IFTA and serve as biomarkers of renal outcome in patients with advanced DKD.